Comparative Effects of Core Stability Exercises and Obstacle Gait Training on Balance in the Elderly Population: A Randomised Controlled Study (International Journal of Physiotherapy, 2025)
Background: Age-related declines in balance, postural control, and muscle strength significantly increase the likelihood of falls among the elderly, often leading to functional limitations and reduced independence. Core Stability Exercises and Obstacle Gait Training are commonly recommended to address these deficits, but comparative evidence on their effectiveness remains limited. This study aimed to evaluate and compare the effectiveness of Core Stability Exercises and Obstacle Gait Training in minimizing fall risk, improving balance, and enhancing functional independence in daily activities among the elderly population.Methods: A total of 52 participants aged 65–75 years with documented balance difficulties were recruited and randomly assigned into two groups. Group A received both Core Stability Exercises and Obstacle Gait Training, while Group B received Obstacle Gait Training alone. The intervention lasted 6 weeks, with sessions held 3 times per week. Outcome measures were assessed using the Berg Balance Scale (BBS) and Fullerton Advanced Balance (FAB) Score, before and after the intervention. Appropriate statistical tests, including Paired and Independent t-tests, were used for data analysis with significance set at p < 0.05.Results: Both groups demonstrated statistically significant improvements in BBS and FAB scores post-intervention (p < 0.0001). However, Group A, which received combined Core Stability Exercises and Obstacle Gait Training, showed greater improvements in balance compared to Group B. Additionally, some participants in Group A progressed from requiring walking aids to ambulating independently for short distances.Conclusion: The study concludes that while Obstacle Gait Training alone is efficacious in improving balance, the combination of Core Stability and Obstacle Gait Training yields superior results in enhancing postural control and functional mobility in older adults. Incorporating these targeted, evidence-based interventions can significantly reduce fall risk, promote independence, and improve the quality of life in the geriatric population.